2011
DOI: 10.4269/ajtmh.2011.11-0186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Drought on the Spatial Pattern of Transmission of Schistosoma haematobium in Coastal Kenya

Abstract: We analyzed temporal changes in spatial patterns of active Schistosoma haematobium infection in different age groups and associated them with ponds infested with Bulinus snails. A major drought between 2001 and 2009 resulted in drying of ponds that were known sources of infection, and we detected very few or no snails in ponds that were infested in the past. The household-level spatial pattern of infection for children of various age groups in 2009 was contrasted with historical data from 2000. The significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
1
22
1
Order By: Relevance
“…Striking inter-village differences were found for cytokine levels and morbidity outcomes, suggesting a clustering effect possibly related to geographical transmission patterns and nutritional and/or socioeconomic disparities. 16,17 This highlights the multi-dimensional approaches needed to understand schistosomiasis infection and disease in the context of other endemic parasitic infections, 18 and the social determinants of health that remain so far unexplored in this field. The unforeseen lack of association between schistosomiasis-associated morbidities (anemia, wasting, and stunting) and pro-inflammatory cytokines previously seen in other endemic settings 5,18,19 might be explained by the intrinsic plasma level variability of cytokine levels when compared with laboratory responses seen in antigen T-cell-stimulating assays performed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Striking inter-village differences were found for cytokine levels and morbidity outcomes, suggesting a clustering effect possibly related to geographical transmission patterns and nutritional and/or socioeconomic disparities. 16,17 This highlights the multi-dimensional approaches needed to understand schistosomiasis infection and disease in the context of other endemic parasitic infections, 18 and the social determinants of health that remain so far unexplored in this field. The unforeseen lack of association between schistosomiasis-associated morbidities (anemia, wasting, and stunting) and pro-inflammatory cytokines previously seen in other endemic settings 5,18,19 might be explained by the intrinsic plasma level variability of cytokine levels when compared with laboratory responses seen in antigen T-cell-stimulating assays performed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we present our findings from four villages in coastal Kenya known to be coendemic for Schistosoma haematobium, STH, Plasmodium falciparum, and Wuchereria bancrofti. 1,[20][21][22][23][24] …”
Section: Introductionmentioning
confidence: 99%
“…Infections are sustained by the high presence of Bulinus species of freshwater snails which are the vectors for S. haematobium [19]. Earlier studies reported a high prevalence of infection in the area; 33.4% [6], 18.2% [20], 43.2% [21], 32.4% [22] and 53.8%, [23]. Infection rate in the current study was significantly higher in women of younger age group 18-23 and 24-29 years.…”
Section: Discussionmentioning
confidence: 99%